Lewis Carroll : Formed by Faith - Lovett, Charlie, 1962- (Book collections on Project MUSE., 2022)
"Examining Charles Lutwidge Dodgson's (Lewis Carroll's) religious education and core beliefs, the book shows that a deep Christian faith undergirded every part of his life and work, from his relationships with children to his writings, his work on logic, and his photography"--